N-Acylsaccharins: Stable Electrophilic Amide-Based Acyl Transfer Reagents in Pd-Catalyzed Suzuki-Miyaura Coupling via N-C Cleavage - Liu, Chengwei; Meng, Guangrong; Liu, Yongmei; Liu, Ruzhang; Lalancette, Roger; Szostak, Roman; Szostak, Michal (Organic letters, 2016)
The development of efficient catalytic methods for N-C bond cleavage in amides remains an important synthetic challenge. The first Pd-catalyzed Suzuki-Miyaura cross-coupling of N-acylsaccharins with boronic acids by selective N-C bond activation is reported. The reaction enables preparation of a variety of functionalized diaryl and alkyl-aryl ketones with broad functional group tolerance and in good to excellent yields. Of general interest, N-acylsaccharins serve as new, highly reactive, bench-stable, economical, amide-based, electrophilic acyl transfer reagents via acyl-metal intermediates. Mechanistic studies strongly support the amide N-C(O) bond twist as the enabling feature of N-acylsaccharins in the N-C bond cleavage.